Freedom of the press and perceptions about government corruption. Issue 4 (September 2020) - Flavin, Patrick; Montgomery, Fielding
The media can play an important role in the relationship between citizens and their government by acting as a watchdog and providing timely information about malfeasance and corruption. We examine whether citizens' perceptions of government corruption are closer to country experts' assessments in countries where there are higher levels of press freedom. Using data on citizens' perceptions of government corruption and country expert evaluations of levels of political corruption for over 100 countries, we present evidence that the relationship between expert measures of corruption and citizens' perceptions is heightened as the level of press freedom increases across our sample. These findings suggest that a free press can play an important role in bringing corruption to light, educating citizens, and potentially allowing them to better hold their elected officials accountable.